Dates' Impact on Lowering Blood Pressure in Hypertension Patients - Khairunnisa Batubara; Elvipson Sinaga (Malahayati Nursing Journal, 2026)
ABSTRACT When the systolic pressure is greater than 130 mmHg and the diastolic pressure is greater than 85 mmHg, the condition is known as hypertension or high blood pressure.  Heart attack consequences can result from hypertension, including impaired renal function, vascular disease, and stroke development.  Modern hypertension drugs might have negative side effects, therefore using a natural remedy, like dates, is an option. Dates are one of the alternative treatments for hypertension that may be found in traditional medicine. This study sought to ascertain whether providing dates to hypertensive individuals could lower their blood pressure. There was a pre-test and post-test control group in this quasi-experimental study design.  Thirty responders were chosen using inclusion criteria and purposive sampling to make up the sample.  While the control group (n=15) simply received standard therapy, the intervention group (n=15) received seven dates per day for 14 days.  A sphygmomanometer was used to assess blood pressure both before and after the intervention.  A paired t-test and an independent t-test with α=0.05 were employed in the analysis. According to the results, the intervention group's systolic and diastolic blood pressures were significantly lower than those of the control group (p0.05). In conclusion, giving dates to hypertension patients is a successful supportive non-pharmacological therapy for lowering blood pressure. Keywords: Blood Pressure, Hypertension, Dates.